2019
DOI: 10.1007/s00330-019-06232-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between quantitative assessment of contrast enhancement in contrast-enhanced spectral mammography (CESM) and histopathology—preliminary results

Abstract: ObjectivesContrast-enhanced spectral mammography (CESM) is a novel method for breast cancer detection. The aim of this study is to check if there is a possibility of quantitative assessment of contrast enhancement in CESM and if there is any correlation between quantitative assessment of contrast enhancement in CESM and histopathology.MethodsA total of 167 female patients underwent CESM. All subjects previously had suspicious lesions found on mammography, breast ultrasound, or both. After imaging, the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 9 publications
5
37
0
Order By: Relevance
“…For enhancement intensity, this preliminary research suggested that enhancement intensity of malignancies was usually stronger than that of benign lesions (Table 1), which was consistent with other researchers' findings 6,[11][12][13][14]17 . Lewin et al 6 concluded that 84.6% (11/13) of invasive cancers enhanced strongly, while all benign lesions (n = 12) were presented as no or weak enhancement qualitatively.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…For enhancement intensity, this preliminary research suggested that enhancement intensity of malignancies was usually stronger than that of benign lesions (Table 1), which was consistent with other researchers' findings 6,[11][12][13][14]17 . Lewin et al 6 concluded that 84.6% (11/13) of invasive cancers enhanced strongly, while all benign lesions (n = 12) were presented as no or weak enhancement qualitatively.…”
Section: Discussionsupporting
confidence: 90%
“…Rudnicki et al 12 and our researches took a quantitative method to evaluate enhancement intensity of lesions on the both two projections (CC and MLO views). Rudnicki et al adopted the percentage signal difference between enhancing lesion and background (%RS) to value the intensity of lesions, which was similar to CNR index in this research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations